Analisis pergeseran lateral dinding turap pada tanah berlapis akibat penggalian pada model dua dimensi - ACHMAD, Fadly ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Lateral displacement caused by soil excavating in sheet pile construction is a complex problem of geotechnical field. The structure of excavation will be unbalanced because horizontal support from the soil has been removed. This research is observed the mechanism of sheet pile’s movement that caused by soil excavating. The model of experiment observed consist of two soil layers. Sticks aluminum were used to model the granular soil in two dimensions and to observe the movement of soil. Bottom layer used soft clay because clay’s movement is too small. The experiments have some variations, first sheet pile without anchor and sheet pile with anchor. Length of sheet pile is vary in 15 cm, 20 cm, 25 cm and 30 cm. The anchor’s construction was set down in certain soil depth. The results of these experiments will compare to the finite element analysis which program is Plaxis. The result of this research shows that the behavior of sheet pile without anchor have been rotated in bottom excavation while sheet pile with anchor have been translated. The behavior of soil deformation in laboratory-observed was same as the soil deformation under Plaxis analysis where soil behind the sheet pile was trend to move to the excavation and gradually smaller by distance to sheet pile. The results of displacement calculation by Plaxis in sheet pile without anchor show that difference percentage of displacement are 27% to 51%. In other side, the results of displacement calculation by Plaxis in anchor sheet pile show that difference percentage of displacement are 24% to 50%. Horizontal displacement of sheet pile by Plaxis analysis is smaller than the observation’s both in sheet pile with anchor and without anchor. This result is due to Plaxis program. Granular soil density in Plaxis was same in all depth. It was contrary in laboratory observed that soil behind sheet pile lean to expand. Keywords : sheet pile, granular soil, clay, displacement sheet pile, soil deformation.